Artificial Intelligence And The Jobs Of The Future: Preparing Young Moderates For Change - Nur Kumala Dewi; Abdul Jamil; Fisa Wisnu Wijaya (Publikasiku, 2024)
The rapid development of artificial intelligence (AI) is bringing major changes to various aspects of life, including the world of work. AI-driven automation and robotization is predicted to replace many jobs currently performed by humans raising concerns about the future of work, especially for the younger generation. This research aims to understand how AI will influence the world of work in the future and how character education and religious moderation can help the younger generation in facing these changes. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. . The results show the ethical, social, and educational challenges that come with the development of AI, as well as the educational strategies and policies needed to prepare the younger generation. Cross-sector collaboration is key in meeting these challenges, with governments, educational institutions, and the private sector working together to ensure that future generations have a strong foundation to face the AI era with confidence and success. Thus, the importance of concerted efforts in preparing the younger generation for an AI-influenced future in Multi Racial PD.